2016
DOI: 10.4254/wjh.v8.i15.637
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen clearance in inactive hepatitis B surface antigen carriers treated with peginterferon alfa-2a

Abstract: IFN treatment results in HBsAg loss and seroconversion in a considerable proportion of inactive HBsAg carriers with low HBsAg concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
7
25
2
Order By: Relevance
“…HBeAg seroconversion and HBsAg loss are two important clinical end‐points in treatment of CHB and predict improved survival with a markedly decreased risk for cirrhosis and HCC. HBsAg seroconversion is often considered the best measurable indicator of viral clearance and recovery, although the rate of HBsAg seroconversion, whether spontaneous or on antiviral therapy is rather low . Recent studies have indicated that a lower HBsAg level and HBV DNA level at baseline and older age may predict HBsAg loss .…”
Section: Discussionmentioning
confidence: 99%
“…HBeAg seroconversion and HBsAg loss are two important clinical end‐points in treatment of CHB and predict improved survival with a markedly decreased risk for cirrhosis and HCC. HBsAg seroconversion is often considered the best measurable indicator of viral clearance and recovery, although the rate of HBsAg seroconversion, whether spontaneous or on antiviral therapy is rather low . Recent studies have indicated that a lower HBsAg level and HBV DNA level at baseline and older age may predict HBsAg loss .…”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytoid dendritic cells (pDC) are the most important cells to connect innate and adaptive immune responses, and also the main source of interferon (IFN)-α. [ 4 ] IFN-α can suppress the activity of HBV enhancers,[ 5 ] control HBV-posttranscriptional replication,[ 6 7 8 ] and inhibit HBV nucleocapsid formation in virus replication. [ 9 ] It can also limit virus infection by modulating both innate and adaptive immunity, directly activate natural killer (NK) cells to enhance their cytotoxicity to eliminate-infected cells, promote the maturation of DCs, stimulate naive cluster of differentiation antigen 8+ (CD8+) T cells, resulting in clonal expansion and proliferation, and increase expression of chemokines that recruit NK, T and B cells to the site of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our study suggested that the activated pDC and the elevated IFN level could trigger the immune response against HBV in chronic hepatitis development from IT, and it might be the basis for those patients in immune active phase receiving PEG-IFN therapy to achieve a higher rate of HBeAg seroconversion and sustained response. [ 7 43 44 ] With the increasing of IL-10 and TGF-β2 contents in chronic hepatitis patients, it might limit virus clearance and lead low rate of spontaneous HBeAg seroconversion in nature history. [ 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…IFN-α is an important antiviral active cytokine and widely used for the treatment of chronic HBV infection. [ 7 8 9 ] IFN-γ is the most important cytokine of cytotoxic T lymphocyte for controlling HBV replication or eradicating HBV in a noncytolyticmanner. [ 10 ] Fms-like tyrosine kinase 3 ligand (Flt-3L) is also an essential growth factor for DC cells and NK cells homeostasis in vivo .…”
Section: Introductionmentioning
confidence: 99%